1980
DOI: 10.3739/rikusui.41.75
|View full text |Cite
|
Sign up to set email alerts
|

Growth Kinetics of Freshwater Bacterial Populations and Isolated Strains

Abstract: The relations between growth rate (ƒÊ, h-1) and organic nutrient concentrations (S,mg/l were examined by using natural bacterial populations and isolated strains in Lake Biwa. The kinetic Hiruta, Tamaki-cho, Watarai-gun,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1985
1985

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Their bacterial floras also showed the highest diversity during October and November, when suspended particles such as dead organisms and detritus seemed to increase with decreasing algal biomass. SIMIDU et al (1971SIMIDU et al ( , 1977, RAMSAY (1977), SOCHARD et al (1979), MATSUDA (1974), andTANAKA et al (1980) evidenced clear differences in the bacterial floras developed on different kinds of suspended particles, such as phytoplankton, zooplankton, particulate detritus, and particulate inorganic matter, in natural aquatic environments. FU-KAMI et al (1981), KOGURE et al (1982), and reported that the particle-associated bacterial flora fluctuated during the decomposition process of phytoplankton cells or detritus particles under experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Their bacterial floras also showed the highest diversity during October and November, when suspended particles such as dead organisms and detritus seemed to increase with decreasing algal biomass. SIMIDU et al (1971SIMIDU et al ( , 1977, RAMSAY (1977), SOCHARD et al (1979), MATSUDA (1974), andTANAKA et al (1980) evidenced clear differences in the bacterial floras developed on different kinds of suspended particles, such as phytoplankton, zooplankton, particulate detritus, and particulate inorganic matter, in natural aquatic environments. FU-KAMI et al (1981), KOGURE et al (1982), and reported that the particle-associated bacterial flora fluctuated during the decomposition process of phytoplankton cells or detritus particles under experimental conditions.…”
Section: Discussionmentioning
confidence: 99%